Leveraging Skype in the Classroom for Science Communication: A Streaming Science – Scientist Online Approach - Peyton N Beattie; Jamie Loizzo; Kevin Kent; Christine L. Krebs; Teresa Suits; J. C. Bunch (Journal of Applied Communications, 2020)
A growing need exists to identify, implement, and research alternative methods to communicate with, educate, and engage youth about science, in order to increase science literacy and knowledge of future societal decision-makers. Electronic field trips (EFTs) are one channel of non-formal communication and education that have been introduced in agricultural and natural resources to reach youth audiences with science-based information in real-time. EFTs can be conducted in several different ways due to the proliferation of video production and web-streaming technologies. The following professional development article offers science communication professionals and scientists a detailed model and specific steps to develop and host an EFT via the Skype in the Classroom platform. The outlined model builds off of prior application and research from the Streaming Science online science communication platform and offers a secondary model for effective EFT implementation and research. The authors describe the establishment of an online science communication network, the development of the Streaming Science: Scientist Online format, content creation, the production team structure, and mobile production hardware and software. Scientist Online EFT program outcomes in terms of participation are noted, as well as student outcomes in the form of excerpts to demonstrate student engagement are shared.
Keywords: electronic field trip (EFT); Skype in the Classroom; science communication; Streaming Science; Scientist Online